(untitled) - Daly, Herman E. (Cheltenham, UK, 1999)
In this controversial new book Herman Daly, a leading commentator on the environment, offers lively criticism of existing work on ecological economics and the economics of ecology. The theme throughout the book is about changes in perspective, attitudes and policies required to avoid uneconomic growth - that is, the impoverishment that results when the environmental and social costs of growth exceed the benefits.
Keywords: Environmental economics